A comparison of shear stress estimation methods for a single geobag on a rough bed. Issue 6 (December 2022) - White, Kendra; She, Yuntong; Zhang, Wenming
Abstract: There are several methods for estimating bed shear stress in the literature, but comprehensive comparisons among them are limited and under specific conditions. This study compared these methods first on a bare smooth bed, and then for a single geobag on a rough bed in the interest of determining the stability of geobags used in riverbank protection structures. The geobag was filled with cement or sand and tested under different open channel flow conditions. The turbulent kinetic energy method appeared to best represent the local bed shear stress on the geobag when using the newly calibrated proportionality constants. The Reynolds stress method via extrapolation was relatively unaffected by changes to the geobags shape and measurement locations, suggesting this method inadequately represents the local bed shear stress. The Patel method and the universal law of the wall method failed to represent local bed shear stress in the rough bed cases due to instrument limitations and the breakdown of the law of the wall. This study highlights the impact of different methods on the bed shear stress estimation. Highlights: Five bed shear stress estimation methods were compared for a geobag on rough bed. Law of the wall assumption breaks down in complex flow conditions. Reynolds stress method fails to represent changes to geobag shape. Turbulent Kinetic Energy method best represented local bed shear stress on geobag. New proportionality constants were estimated for Turbulent Kinetic Energy methods.